Effects of exercise modalities on heart rate recovery and its association with cardiometabolic risk in adolescents with overweight or obesity - Rubin Pooni; Silva Arslanian; Heather Edgell; Hala Tamim; Sojung Lee; Jennifer L. Kuk (PLoS ONE, 2025)
Objective Attenuated heart rate recovery (HRR) immediately after exercise is an independent predictor of cardiovascular disease and mortality in adults. We examined the effects of aerobic exercise (AE), resistance exercise (RE), and combined AE and RE on HRR, and the relationship of HRR with body composition and metabolic risk factors in adolescents with overweight or obesity. Research design and methods We included 147 adolescents (BMI ≥ 85 th percentile, 12–18 years) who participated in exercise intervention studies (3–6 months), and had a complete data set including VO 2peak , body composition by dual-energy X-ray absorptiometry, and cardiometabolic risk factors before and after the interventions. HRR was calculated as the difference between peak HR during the maximal treadmill test and HR at 1-, 2-, 3-, 4-, and 5-min after the cessation of the test. Results After interventions, a faster HRR at 2–5 min was observed following AE (17.3–25.6% change, P < 0.0001), RE (7.1–10.9%, P < 0.05), and combined AE and RE (10.7–12.0%, P < 0.05) compared to pre-intervention. Compared to controls, AE (14.0–24.0%, P < 0.05) was the only exercise group to exhibit a significantly faster HRR at 1-, 2-, 3-, 4-, and 5-min after the exercise intervention. Collapsed across exercise groups, improvements in 2-, 3-, 4-, and 5-min HRR are independently associated ( P < 0.05) with increases in VO 2peak . Changes in HRR were not associated with the changes in % body fat or metabolic risk factors. Conclusion AE training is more beneficial than RE or combined AE and RE training for improving HRR in adolescents with overweight or obesity.